Benefits of a Root Fungal Endophyte on Physiological Processes and Growth of the Vulnerable Legume Tree Prosopis Chilensis (Fabaceae) - Urzua-Moll, A; Gonzalez-Teuber, M (Oxford University Press, 2018)
Aims: Desertification is a major concern in arid and semi-arid regions globally. Understanding interactions between vulnerable plant species and associated microbial symbionts may have important applications for conservation and restoration strategies in affected areas. Methods: In this study, we evaluated the root-associated fungal endophyte community in Prosopis chilensis, a vulnerable and threatened arid-adapted tree of northern Chile. Host benefits in terms of physiological performance and plant growth were also assessed. Endophytic fungi were isolated from asymptomatic roots by the culture method for molecular identification of the 18S rRNA gene. The dominant fungal endophyte (Penicillium sp.) in the community was later used in inoculation experiments to assess its effect on maximum quantum efficiency of photosystem II (PSII), (Fv/Fm) actual PSII efficiency (Φ PSII ), and non-photochemical quenching (NPQ). Total sugars, starch content, malonaldehyde (MDA), nitrogen content (%) and growth traits were also measured. Important Findings: Whereas Φ PSII increased significantly in endophyte-inoculated plants, NPQ was found to decrease. No effect of endophyte inoculation on sugars and MDA was detected, but starch content, leaf nitrogen content, number of leaves and shoot biomass were found to increase. Results revealed that inoculation of endophytic Penicillium fungal isolate can provide significant physiological benefits to the host plant P. chilensis. Its presence resulted in greater PSII efficiency and higher leaf nitrogen and carbohydrate content, enhancing host plant growth. These findings highlight the importance of considering the fungal endophyte community of this vulnerable species as an important tool to the design of further revegetation and conservation programs. © 2018 The Author(s).